Analysis of Translation Techniques for Interrogative Sentences in the Subtitles of the Film Ernest et Célestine - Elia Nugraheni,; Dudung Gumilar,; Farida Amalia, (RETORIKA: Jurnal Ilmu Bahasa, 2025)
Translating interrogative sentences is crucial to preserving the original dialogue's meaning and nuance, as well as conveying emotions such as curiosity or affirmation to the audience. This study aims to analyze the ideology, methods, and translation techniques used and the acceptability of the translated texts of interrogative sentences in Ernest et Célestine. Research on interrogative sentences is still limited, especially in animated films like Ernest et Célestine. Most of the previous studies discuss translation broadly without focusing on interrogative sentences. Using the descriptive qualitative method, this research analyzes and descriptively present the ideology, methods, and techniques used in translating interrogative sentences. In this study, the researcher will classify interrogative sentences based on Anne Dagnac's theory (2024), then analyze the translation ideology based on Venuti's theory and Newmark's translation method (1988) in Siregar (2017), and Molina and Albir's translation technique (2002) in Emzir (2015). The study identifies four translation technique combinations: single, duplet, triplet, and quartet. Among the 18 analyzed samples, domestication was the translation ideology used. The most frequently used translation methods were communicative translation (16 cases), followed by free translation (1 case) and literal translation (1 case). Eight translation techniques were identified, including reduction, common equivalence, adaptation, modulation, amplification, transposition, borrowing, and literal translation. The triplet technique was the most common, followed by quartet, duplet, and single techniques. The translation of interrogative sentences in Ernest et Célestine prioritizes domestication to improve acceptability in the local cultural context, achieved through a combination of translation methods and techniques